2005
DOI: 10.1007/s00464-003-9276-5
|View full text |Cite
|
Sign up to set email alerts
|

The value of endoscopic diagnosis and the treatment of pancreas injuries following blunt abdominal trauma

Abstract: The major advantage of the prompt retrograde discription of the pancreatobiliary system after an accident in which pancreas involvement is suspected is the more precise assessment of the extent of the injuries. If a stent is placed in the same session, it is possible to carry out definitive and interventional treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 23 publications
0
59
2
1
Order By: Relevance
“…The ERCP scores not only the diagnosis but it also can rule out pancreatic injury. It is possible to spare patients an operation by placing a stent during the same session and carry out definitive and interventional treatment [13]. Its application is limited, especially in the acute trauma situation, as it can only be performed in stable patients and requires an experienced endoscopist [7,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The ERCP scores not only the diagnosis but it also can rule out pancreatic injury. It is possible to spare patients an operation by placing a stent during the same session and carry out definitive and interventional treatment [13]. Its application is limited, especially in the acute trauma situation, as it can only be performed in stable patients and requires an experienced endoscopist [7,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Uncommonly used as a first-line test, ERCP becomes useful in patients with delayed presentation (with the late onset of pain or post-traumatic pseudocysts) [30,[34][35][36]. Houben et al [37] reported on 15 pediatric trauma patients with pancreatic injuries all of whom but two presented with a delay.…”
Section: Diagnosismentioning
confidence: 99%
“…Surgery may be totally avoided [4,22,23]. Because of the rarity of posttraumatic duct disruption, the series are small.…”
Section: Endoscopic Interventionsmentioning
confidence: 99%